2005
DOI: 10.1002/prot.20541
|View full text |Cite
|
Sign up to set email alerts
|

Structural analysis of a set of proteins resulting from a bacterial genomics project

Abstract: The targets of the Structural GenomiX (SGX) bacterial genomics project were proteins conserved in multiple prokaryotic organisms with no obvious sequence homolog in the Protein Data Bank of known structures. The outcome of this work was 80 structures, covering 60 unique sequences and 49 different genes. Experimental phase determination from proteins incorporating Se-Met was carried out for 45 structures with most of the remainder solved by molecular replacement using members of the experimentally phased set as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
192
1
3

Year Published

2007
2007
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 228 publications
(212 citation statements)
references
References 49 publications
14
192
1
3
Order By: Relevance
“…4) has been determined (17). The proximity of the Mes sulfonic acid group to Cys-94 and the disulfide bond between Cys-84 and Cys-118 is reminiscent of the arrangement of active site residues in bMsrA and eMsrA (4,14).…”
Section: Discussionmentioning
confidence: 99%
“…4) has been determined (17). The proximity of the Mes sulfonic acid group to Cys-94 and the disulfide bond between Cys-84 and Cys-118 is reminiscent of the arrangement of active site residues in bMsrA and eMsrA (4,14).…”
Section: Discussionmentioning
confidence: 99%
“…Hunt, unpubl. ), TM0844 from Thermotoga maritima (PDB 1o6d) (Badger et al 2005), and SAV0024/SA0023 from Staphylococcus aureus (PDB 1vh0) (Badger et al 2005). The proteins display an unusual knotted structure.…”
Section: A Mechanistic Model For Ybea Activitymentioning
confidence: 99%
“…Crystal structures of RsmE family proteins from Haemophilus influenzae (YggJ, PDB entry 1NXZ; Forouhar et al 2003), Bacillus subtilis (YqeU, PDB entry 1VHK; Badger et al 2005), Thermotoga maritima (Tm1380, PDB entry 1Z85; http://www.rcsb.org/pdb/), and Thermus thermophilus (Tt1573, PDB entry 1V6Z; Joint Center for Structural Genomics, http://www.rcsb.org/pdb/) have been determined, and indicated that RsmE forms dimers in the crystals. To determine the actual oligomeric state of the E. coli protein in solution, we analyzed purified His-RsmE by gel filtration chromatography on a Superose-6 column.…”
Section: Physical Proprieties Of Rsme and His-rsmementioning
confidence: 99%